Studying sorption properties of a mixture of natural and synthetic zeolites in respect of radionuclides ¹³⁷Cs and ⁹⁰Sr - Lonin, A.Ya.; Krasnopyorova, A.P. (Вопросы атомной науки и техники, 2009)
Sorption properties of a mixture of zeolites (natural and synthetic) in respect of radionuclides ¹³⁷Cs and ⁹⁰Sr are studied. The influence of additions on the sorption properties of clinoptilolite and mixture of zeolites (natural and synthetic) is studied.